A revision of the Dwarf Geckos, genus Lygodactylus (Squamata: Gekkonidae), from Angola, with the description of three new species - Marques, Mariana P.; Ceríaco, Luis M. P.; Buehler, Matthew D.; Bandeira, Suzana A.; Janota, Joyce M.; Bauer, Aaron M. (Zootaxa, 2020)
At present the genus Lygodactylus is represented by three species in Angola confirmed by voucher specimens—L. angolensis, L. bradfieldi, and L. capensis—and two others believed to be present, but without specimens with precise localities, L. chobiensis and L. lawrencei. We present a detailed taxonomic revision of the group in Angola and describe three new species, Lygodactylus baptistai sp. nov. L. nyaneka sp. nov. and Lygodactylus tchokwe sp. nov. Phylogenetic analysis using the mitochondrial marker ND2, as well as morphological data support the recognition of the new species. In addition, data suggest that specimens historically assigned to L. capensis in Angola represent misidentifications of L. nyaneka sp. nov. and L. tchokwe sp. nov. We revisit the identity of Lygodactylus laurae, a junior synonym of L. angolensis. We also present the first confirmed record of L. lawrencei in the country, using both morphological and molecular data. The description of the new species and the revision of the taxonomic identity of the Angolan populations of the genus, raises the number of species occurring in the country to five. A key to the Angolan species is presented.